1996
DOI: 10.1046/j.1365-2133.1996.d01-1090.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of glycoprotein lib is present in metastasized but not in non-metastasized primary malignant melanoma

Abstract: Glycoprotein IIb-IIIa (integrin alpha IIb beta3) is an adhesive receptor involved in platelet aggregation and adhesion to the extracellular matrix. Previous studies showed the presence of IIb-IIIa-like glycoproteins on cells of melanoma cell lines and on cells of lymph node metastases. This study evaluates the presence of glycoprotein IIb-IIIa subunits on cells of primary cutaneous malignant melanomas with (n = 4) and without (n = 9) metastases over a period of 6 years and on naevus cells (n = 4). Monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Ectopic expression of αIIbβ3 in melanoma cells that endogenously express αvβ3 increases their tumorigenic and metastatic ability to selected organs [85]. This is further supported by pathologic studies demonstrating that αIIbβ3 expression directly correlated with melanoma thickness, an indicator of metastatic potential [40, 43, 85]. …”
Section: Involvement Of Thrombocytic Genes and The Clotting System Insupporting
confidence: 52%
See 2 more Smart Citations
“…Ectopic expression of αIIbβ3 in melanoma cells that endogenously express αvβ3 increases their tumorigenic and metastatic ability to selected organs [85]. This is further supported by pathologic studies demonstrating that αIIbβ3 expression directly correlated with melanoma thickness, an indicator of metastatic potential [40, 43, 85]. …”
Section: Involvement Of Thrombocytic Genes and The Clotting System Insupporting
confidence: 52%
“…Data indicate that heparin can directly bind αIIbβ3, the predominant integrin of platelets [113, 114]. On the other hand, several human tumor cell types express ectopic αIIbβ3 integrins (see above) [35,36,37,38,39,40,41,42,43] involved in invasion and metastasis. Therefore, megakaryocytic integrin could be another molecular target of heparin.…”
Section: Preclinical Evidence Of the Specific Antimetastatic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of MMP7 production may be also related to the less invasive characteristics of the metastatic brain tumors compared with the highly invasive glioblastoma. Although a large number of extracellular matrix molecules can promote the migration of tumor cells, the function of only a few tumor cell receptors may be critical in brain metastasis [27]. CD44 is one of the most abundant molecules in the extracellular matrix of the brain [22].…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies on human samples demonstrated that v 3 integrin expression is constitutive in primary melanomas, while the IIb 3 expression increased with tumor thickness. 8,17 We suggest that in human melanoma, overexpression of v 3 integrin may correlate with VEGF expression, while the emergence of the illegitimate expression of the IIb 3 integrin in a later stage of the disease (vertical growth phase) may contribute to the upregulation of bFGF expression, providing both another autocrine growth factor as well as another angiogenic cytokine for melanoma cells. Parallel expression of the two 3-integrins in human melanoma cells induced modulation not only of bFGF but other genes as well, which is demonstrated by microarray analysis.…”
Section: Discussionmentioning
confidence: 92%